High performance hydrogen selective membranes prepared using rapid processing method - Gopalakrishnan, S.; Nair, Balagopal; Nakao, S. (IEEE Publishing Co, 2006)
The production of hydrogen using membrane based reforming technology is one important application where the membrane is required to withstand high temperatures and pressures to achieve maximum efficiency from an equilibriumlimited reaction. Microporous silica membranes offer a viable alternative to polymer and metal composite membranes. The processing of silica membranes including sol-gel and chemical vapor deposition (CVD) methods are discussed adequately in the literature. The Sol-gel method allows for the precise control of pore structure while CVD results in chemically homogenous deposits inside the porous substrates to yield better selectivity. The main problem associated with these methods is the long processing times to prepare these membranes, resulting in increased cost of production for the processing of large batches. Here we report an advance in membrane processing that could drastically reduce membrane processing time without compromising performance.